Budaya Pengucapan Syukur Sebagai Faktor Yang Mendukung Peningkatan Kunjungan Wisatawan dan PAD Provinsi Sulawesi Utara - Trilke Tulung; Gustaf J.E. Undap; Rivo J.D. Sumampouw (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The world of tourism is a very important sector in the development of a region, through tourism, the region can obtain local revenue through tourist visits, in addition, with the many tourists both domestic and foreign, the surrounding community can enjoy the positive impact of the development of home businesses, in addition, therefore it is important for the government to make regulations for the advancement of tourism, especially in North Sulawesi. The study uses a qualitative research method through the stages of field observation, online data searches related to tourism development policies in the Region, especially in North Minahasa Regency and North Sulawesi in general, as well as data findings in the field and also previous studies that have studied matters related to the title of this study, then a focus group discussion is conducted. The targeted output in this study is a National accredited journal ranked 6 in order to achieve the research strategy plan of Sam Ratulangi University and improve the performance of researcher publications in the field of excellence social humanities arts and culture in Sustainable tourism economic development. The level of technological readiness (TKT) in this study is at stage three (Proof-of-concept) of important functions and/or characteristics analytically and experimentally. The technology used in this study certainly adjusts to the needs that will be used in the field later and also to analyze the data it can be seen that the technology needed in this study is easy to find in the North Sulawesi region